Obstetric care under the military health system: An analysis of active-duty women’s and female spouses’ online discussions - Amanda M. Rebhi (Qualitative Research in Medicine & Healthcare)
This research undertakes a thematic analysis of discussion threads on social media forums to determine women’s perceptions of quality of obstetric care under TRICARE Prime and TRICARE Select. Following an open coding process and thematic analysis, themes arose regarding obstetric care as experienced by active-duty women as well as female spouses of active-duty members. Themes surrounding active-duty perceptions of quality of obstetric care concerned proximity to care deferred deliveries, lack of care options, deficient on-base care, better civilian care experiences, and lamenting having less options than spouses. Spouses generated themes of positive connotation with TRICARE Select, including low costs, freedom of choice, and proximity to care and negative connotation with TRICARE Prime, such as difficulty getting care, process bureaucracy, and deficient care. Ample evidence pointed to a strong spouse preference for TRICARE Select over TRICARE Prime, but there was not enough evidence to indicate if active-duty women were pursuing out-of-pocket care to circumvent TRICARE Prime restrictions. Overall, women’s discussions point to a need to improve the Military Health System and concerningly suggest active-duty women are confined to care within a system plagued with issues that impact obstetric care.